Parent Training Program for Autism Spectrum Disorder During The Covid-19 Pandemic Period in Indonesia - Ina Dewi Ardiyani; Nining Febriyana; Yunias Setiawati; Royke Tony Kalalo (Jurnal Psikiatri Surabaya, 2020)
Autism Spectrum Disorder (ASD) is a pervasive developmental disorder that shows difficulties in communication, social interaction, behavior, interests and activities that are limited and repetitive. The prevalence of ASD also continues to increase worldwide, followed by an increase in the need for early intervention in ASD children. The limited services available make early intervention a challenge in itself. The long Covid-19 pandemic has resulted in limited therapy, because therapy in treatment service facilities cannot be carried out as before. In this case it is important to involve parents as the primary caregivers for ASD children in interventions to anticipate the limited interventions due to a pandemic situation. Parent Training can be done as an effort to provide information, education, and skills to parents so that they can provide intensive, comprehensive, sustainable, and early intervention.